(untitled) (Scottish Historical and Archaeological Internet Reports, 2007)
Specialist reports on pottery, coarse stone, copper alloy, iron, slag, Roman glass, oil shale and cannel coal, slag and antler. There is also a general discussion of the artefact assemblage as a whole.